The relationship between fiber intake and sedentary lifestyle with the risk of metabolic syndrome in adolescents at SMA Batik 1 Surakarta - Sharla Apsarini Luthfiah; Dwi Sarbini (Journal of Midwifery and Nursing, 2025)
Change pattern eating and style life sedentary contribute to the improvement case disease degenerative, including syndrome metabolic. Syndrome this, which is marked with five criteria (circle waist, glucose blood high, low HDL levels, and triglycerides high), can increase risk disease No contagious. Research This aiming for to study connection between intake fiber, pattern life sedentary, and risk syndrome metabolic disorders in adolescents at SMA Batik 1 Surakarta. Research This is studies observational analytic with cross sectional design, involving 65 selected respondents use proportional random sampling method. Data were collected through interview with SQ-FFQ questionnaire for intake fiber and ASAQ for activity sedentary. Data analysis was carried out using the Chi-Square test to test connection intake fiber and activity sedentary with risk syndrome metabolic.Results study show that No existence connection intake fiber with risk incident metabolic syndrome (p-value = 1.000) and the presence of connection pattern life sedentary with risk incident syndrome metabolic (p-value = 0.035). Teenagers who consume intake fiber Good not enough and also excessive No influence existence risk syndrome metabolic and adolescents who have pattern life sedentary ? 5 hours per day at risk experience syndrome metabolic.